Mulheres negras, produção e interseccionalidade - Silva, Roberta Ribeiro da (2019)
The year of 1492 constitutes itself as a milestone in the construction of the colonial system, which shapes around it the model of civilization that should be followed by all. In this context, any people who were outside of the standardization, either by not submitting themselves to the model or by not being considered worthy of that, would be relegated to the condition of “others”. In this way, the colonial system has engendered exclusive mechanisms in different areas, above all, in the construction of identity, history and knowledge. History, as it has been written since then, privileges the speech and experience lived by the peoples inserted in the crystallized geographics scenario of knowledge production, organizing, classifying and hierarchizing the knowledges. Thus, the colonialism, in the form of the State, regulates the access and permanence of others in these spaces of power. By using the power, the system, besides elaborating mechanisms that hinder the access, also delegitimizes the intellectual production elaborated by the others, not granting them the status of academic research and / or science, creating a false parameter that there is no authorial production of these, different from the vast literature already published on them. In view of the above, the purpose of this study was to investigate, through the mapping of the intellectual production of black women, how the colonial system promotes the silencing of these subjects, an integral part of the others, in the academy. Regarding the methodology, this work moves in the field of qualitative and quantitative research, for using data in the construction of our reflection. During the research, intersectionality provided the necessary instrumentality to construct the argument that was developed in this thesis, making it possible to glimpse that within the constant points of intersection, sometimes the race, sometimes the gender, sometimes the class, sometimes the location produces approximations and / or distances from the structures of intellectual power. In dialogue with the feminist epistemologies and with the decolonial studies, some ways were pointed out for the construction of new forms of knowledge production, dissociating and moving it to the margins